Perencanaan Lanskap Mitigasi Tsunami Berbasis Ekosistem Mangrove di Kota Palu - Mochammad Azkari Hisbulloh Akbar; Faisol Abdul Kharis; Oktavia Putri Rahmawati (http://arl.faperta.ipb.ac.id/, 2020)
The coastal areas are vulnerable areas to disaster threats, especially the geological hazards of earthquakes accompanied by tsunamis. Palu City, which is located on the west coast of Sulawesi, experienced a natural disaster of an earthquake, tsunami, and liquefaction on September 28, 2018. Based on the Map of Disaster Prone Index in Central Sulawesi Province, Palu City is a tsunami-prone area that is crossed by the Palu-Koro Fault. Tsunami disaster mitigation efforts in coastal areas can be done by planting mangrove ecosystems as a green barrier. The purpose of this study is to analyze the characteristics of the coastal landscape in Palu City and plan the landscape of tsunami mitigation based on mangrove ecosystems in Palu City. The method used spatial analysis method and descriptive method, as well as the research stage, consists of preparation, data analysis, data synthesis, and landscape planning stage. The basic concept of tsunami mitigation landscape planning is to reduce or eliminate disaster risk in coastal areas based on mangrove ecosystems. The concept of spatial pattern concept consists of high hazard zones, medium hazard zones, and low hazard zones. The concept of vegetation refers to the diversity of mangrove and native plant species as green open spaces and green barriers.